2016
DOI: 10.1111/pme.12877
|View full text |Cite
|
Sign up to set email alerts
|

Computer Tablet Distraction in Children Receiving an Injection

Abstract: The use of a tablet as a distraction was not effective in decreasing pain and distress in children receiving an injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 18 publications
3
23
1
Order By: Relevance
“…One trial showed that parents reported their children felt less pain when they were distracted by an iPad (13), while another study did not show any effect in decreasing pain when children received an injection (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One trial showed that parents reported their children felt less pain when they were distracted by an iPad (13), while another study did not show any effect in decreasing pain when children received an injection (12).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have drawn attention to the effectiveness of hand-held computers as a form of distraction during painful procedures in children, but there are some gaps that still need to be addressed (11)(12)(13).…”
Section: Key Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Three studies included participants ranging from 4-12, 52-54 one study had 4-5 and 11-13 year-olds. 55 Sample size ranged from 22 to 239 participants, eight studies had fewer than 50 participants, 11,30,32,40,46,48,49,54 10 had between 51 to 100 participants, [33][34][35][36]38,42,44,45,52,55 and nine studies had more than 100 participants. 31,37,39,41,43,47,50,51,53 Twelve studies used single vaccinations, 11,31,35,[37][38][39]41,[47][48][49][50][51] ten studies used more than one vaccination, 30,[32][33][34]40,42,43,45,53,…”
Section: Resultsmentioning
confidence: 99%
“…31,37,39,41,43,47,50,51,53 Twelve studies used single vaccinations, 11,31,35,[37][38][39]41,[47][48][49][50][51] ten studies used more than one vaccination, 30,[32][33][34]40,42,43,45,53,55 and five studies used 'routine vaccinations' without specifying the number. 36,44,46,52,54 Vaccinations that were used included Hepatitis A, Hepatitis B, Diptheria-Tetanus (DT), Diphtheria-Pertussis-Tetanus (DPT/DTP), Diphtheria, Pertussis, Tetanus and Polio (DPTP), Measles, Mumps, and Rubella (MMR), Varicella, Meningococcal and Inactivated Poliovirus (IVP) vaccinations.…”
Section: Resultsmentioning
confidence: 99%